(untitled) (Research, Society and Development, 2020)
Pepper (Capsicum annum) is one of the main vegetables consumed in the Brazilian market, however, an important fungal disease, anthracnose, caused by Colletotrichum gloeosporioides, can decimate all its fruits in the field. Chemical control is the most commonly used measure of control, but, some active ingredients are proving ineffective, and consumers appreciate healthier options such as organic foods. Therefore, studies with natural substances that may help in the management of diseases have been encouraged. Because it is transmitted via seed, seed treatment becomes an essential measure in the management and control of pepper anthracnose. The objective of this study was to evaluate the effect of basil (Ocimum basilicum), citronella (Cymbopogon winterianus), clove (Syzygium aromaticum), copaiba (Copaifera langsdorfii), eucalyptus (Eucalyptus citriodora), mint (Mentha arvensis), rosemary (Rosmarinus officinalis) and tea tree (Melaleuca alternifolia) essential oils on the development of C. gloeosporioides. Citronella, clove, eucalyptus, mint and basil essential oils totally inhibited the pathogen, regardless of the concentration used. These essential oils were then used to treat seeds infected with C. gloeosporioides, evaluating the physiological and health quality of these seeds. Clove essential oil reduced the incidence of fungi in seeds inoculated with the pathogen, without affecting their physiological quality.